Can we have many C-sections - Ghazal, Kariman; Hajjar, Charlote; Yared, Georges; Chahine, Rabih (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
The rate of cesarean section is increasing worldwide. It decreases maternal and fetal mortality when complications happen. However, it is a major surgery that could be associated with maternal and fetal risks especially after repeat cesarean deliveries. We report a case of a woman who had her 9th C-section.